Platinum and Cobalt hydroxide – modified Platinum Electrode as Sensor for Electrochemical Oxidation of Amoxicillin - Herlina, Herlina; Zulfikar, Muhammad Ali; Sirumapea, Lasmaryna; Buchari, Buchari (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2022)
Antibiotics have recently gained in popularity due to their usage in medical treatment and the process of removing them from the environment. Amoxicillin is one of the antibiotics that constitutes the study's subject. On a Pt disc electrode and a cobalt hydroxide modified-Pt electrode, the scan rate and pH in the electrochemical oxidation of amoxicillin were investigated. The voltammetry measurement's current peak revealed that changing the electrode surface could increase the electrochemical response and sensitivity of the working electrodes. The Pt/Co(OH)2 modification working electrode had a high sensitivity in the electro-oxidation determination of amoxicillin, with a linear range of the sensor of 20 to 80 M and a limit of detection of 7.15 M for the Pt disc electrode and 3.64 M for the cobalt hydroxide modified Pt electrode. The findings of determination in real samples with electro-oxidation using a modified electrode were in good agreement with a confidence level of 95 percent, according to the comparing method with HPLC.